Multi-locus sequence typing of Treponema pallidum subsp. pallidum present in clinical samples from France: Infecting treponemes are genetically diverse and belong to 18 allelic profiles - Pospíšilová, Petra; Grange, Philippe Alain; Grillová, Linda; Mikalová, Lenka; Martinet, Pervenche; Janier, Michel; Vermersch, Annie; Benhaddou, Nadjet; Del Giudice, Pascal; Alcaraz, Isabelle; Truchetet, François; Dupin, Nicolas; et al. (PloS one, 2018)
Treponema pallidum subsp. pallidum, the causative agent of sexually transmitted syphilis, detected in clinical samples from France, was subjected to molecular typing using the recently developed Multilocus Sequence Typing system. The samples (n = 133) used in this study were collected from 2010-2016 from patients with diagnosed primary or secondary syphilis attending outpatient centers or hospitals in several locations in France. Altogether, 18 different allelic profiles were found among the fully typed samples (n = 112). There were five allelic variants identified for TP0136, 12 for TP0548, and eight for TP0705. Out of the identified alleles, one, seven, and three novel alleles were identified in TP0136, TP0548, and TP0705, respectively. Partial allelic profiles were obtained from 6 samples. The majority of samples (n = 110) belonged to the SS14-like cluster of TPA isolates while 7 clustered with Nichols-like isolates. Patients infected with Nichols-like samples were more often older (p = 0.041) and more often diagnosed with secondary syphilis (p = 0.033) compared to patients infected with SS14-like samples. In addition, macrolide resistance caused by the A2058G mutation was found to be associated with allelic profile 1.3.1 or with strains belonging to the 1.3.1 lineage (p<0.001). The genetic diversity among TPA strains infecting the European population was surprisingly high, which suggests that additional studies are needed to reveal the full genetic diversity of TPA pathogens infecting humans.
Keywords: Biodiversity; Young Adult; Multilocus Sequence Typing; Male; France; Child, Preschool; mladý dospělý; techniky typizace bakterií; Adolescent; Infant; Child; biodiverzita; dítě; Adult; Aged; dospělí; Francie; senioři; mužské pohlaví; syfilis; mladiství; novorozenec; předškolní dítě; Treponema pallidum; lidé; ženské pohlaví; Humans; Infant, Newborn; kojenec; multilokusová sekvenční typizace; Syphilis; Bacterial Typing Techniques; Alleles; Female; alely; lidé středního věku; Middle Aged